Efek Ultrasonic Assited Extraction Tumbuhan Subclass Asteridae Sebagai Antibakteri - Rahmiati, Rahmiati; Simanjuntak, Helen Anjelina; Br. Sembiring, Heylen Sebryna (Herbal Medicine Journal, 2024)
Asteridae is a group of flowering plants with many species. The UAE method is used to produce high-quality extracts more quickly and reduce the use of solvents. This study aims to determine the effectiveness of Asteridae subclass plants in fighting bacteria. Antibacterial tests were carried out using the diffusion method using disc paper by looking at the clear zone around the disc. The results showed that Erigeron sumatrensis leaf extract can inhibit the growth of staphylococcus aureus bacteria. At a concentration of 30%, the effect is classified as weak, while at concentrations of 50% and 70%, the effect is classified as moderate and a concentration of 100% is classified as strong. Salmonella typhi bacteria at concentrations of 30%, 50%, and 70% are classified as moderate, while at a concentration of 100% it is classified as strong. Stachytarpheta mutabilis leaf extract is effective against Escherichia coli bacteria at concentrations of 30% and 50%, including the moderate category. While at concentrations of 70% and 100% the effect is included in the strong category. Coleus scutellarioides and Strobilanthes crispus leaf extracts had equally strong effects against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Salmonella typhi at concentrations of 30%, 50%, 70%, and 100%.